Divórcio impositivo: da autonomia privada à dignidade humana - SAAD, Sarah Sousa (2022)
The present work aims to problematize the non-agreement of one of the spouses, preventing the dissolution of the marital bond through divorce. At the beginning, considerations about the methodological course of the research are presented, placing it in the bibliographic and documentary analysis of the exploratory type, qualitative approach, deductive reasoning and content analysis in order to analyze the research object: to guarantee the facilitation of the reconstitution of the life of the individual after the end of the conjugal life, through the imposition of divorce. The hypothesis is that the individual, submerged in the circle of guarantee of his private autonomy, will produce the law that will govern the future relationships of his life. Therefore, once the marital relationship is over, this individual, through the imposition of divorce, carried out by the extrajudicial services, will be able to exercise his potestative right, regulated by his own private autonomy, rebuilding his life and no longer staying married. The investigation is structured in the general objective of analyzing the institute of imposing divorce as a phenomenon that guarantees the regularization of the individual's life with the end of the marital relationship, and in the specific objectives of discussing private autonomy in divorce; analyze the institute of tax divorce and understand to what extent tax divorce can contribute to the institutions of the Justice System. The present research is justified by analyzing the imposition of divorce as an institute that aims to guarantee the full exercise of private autonomy, so that the will of this subject can be protected by the State; it is also justified by the perspective of the institute as a modern legal model, capable of providing adequate solutions for current social demands; Finally, in view of the imposition of divorce, the relevance of extrajudicial services to the justice system is emphasized, given that the realization of the institute will, if approved, be carried out in extrajudicial ways. From the results of the research, the hypothesis is confirmed, noting that, if the impositional divorce is approved, the individual, within the space provided by the State, will produce for himself, the law that will regulate his life, that is, your will will be protected. With this, once the marital relationship is over, this subject, through the imposition of divorce, will be able to exercise his potestative right, regulated by his own private autonomy, rebuilding his life and no longer staying married. The general conclusion is that the approval of the imposition of divorce will facilitate not only the procedures of the aforementioned institute, but, above all, the regulation of the individual's life upon divorce.